Development of an energetic demand profile in figure skating - Hermsdorf, M.; Hartmann, U.; Spiegel, S.; Knoll, Ka.; Ehrig, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Existing data for the metabolic background and the endurance skills in figure skating are very incomplete and primarily based on an `old rating system` of the 70s and 80s. They show a high participation of anaerobic and low share aerobic energy for a free skating of four minutes (1, 2). The aim of this study is the development of a complex sport-specific energetic demand profile for figure skating competition. Methods Eleven competitive figure skaters (five males, six females) with the following physical characteristics took part in the study: mean age 16.4 ± 2.5 yrs, mean height 164.5 ± 6.9 cm, mean body weight 56.9 ± 7.5 kg. Ventilation, gas exchange and heart rate (HR) were measured during the free skating presentation for a minimum of four minutes with a portable spirometry system (MetaMax 3B, Cortex, Germany). Lactate concentration (LA) was assessed before and after the exercise (Biosen S_line, EKF-diagnostic, Germany). Additionally, free skating presentation was recorded on video for quantitative analysis. Covered distance and velocity of the figure skater were measured with an local indoor position system (LPM, Inmotio, Netherland, frequency 1.000 Hz, measurement accuracy of 5 cm). Laboratory tests were carried out to determine maximum oxygen uptake (VO2max), HR and LA during a treadmill (Saturn, h-pcosmos, Germany) all-out-test with an increasing workload (start by 3.25 m/s, increase 0.25 m/s every 30 s, inclination 1 %) until exhaustion (vita-maxima-test). Results: All athletes reached their individual maximum HR and VO2max during the four minutes free presentation on ice. In average VO2max (n=6) was 3.21 ± 0.69 l/min on ice and 3.19 ± 0.68 l/min on treadmill, corresponding to 59.0 ± 7.4 ml/kg/min and 58.3 ± 6.1 ml/kg/min respectively. HR was 194.0 ± 7.7 min-1 on ice and 198.0 ± 4.1 min-1 on treadmill and LA 9.7 ± 2.5 mmol/l and 10.1 ± 3.1 mmol/l. The analyses of the gas exchange parameters indicate a distribution 74.1 ± 5.1 % of aerobic, 11.6 ± 2.9 % anaerobic lactic and 14.3 ± 3.6 % anaerobic alactic energy shares. Discussion: The results point out to a very high aerobic metabolic rate in free skating for top competitors. All athletes showed very high physical strain during free skating. However, the data of the acyclic activity profile on ice implies that aerobic metabolism is the dominant source of energy. Compared to traditional perspectives, as mentioned in the introduction, the anaerobic shares take up a minor influencing factor